Reduced lung cancer mortality and exposure to synthetic fluids and biocide in the auto manufacturing industry - Mehta, Amar J; Malloy, Elizabeth J; Applebaum, Katie M; Schwartz, Joel; Christiani, David C; Eisen, Ellen A (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'Water-based soluble and synthetic metalworking fluids (MWF) used in auto manufacturing may be contaminated by endotoxin from Gram-negative bacteria, a possible anticarcinogen via increased immunosurveillance. The effectiveness of biocide, generally added to limit bacterial growth is unknown. We investigated whether an inverse relationship between lung cancer and synthetic MWF and biocide – as surrogates of endotoxin exposure – persisted in an extended follow-up of autoworkers. ' ' METHODS ': 'A nested case–control analysis was performed within a retrospective cohort study of 46 399 auto manufacturing workers. Follow-up began in 1941 and was extended from 1985–1995. Mortality rate ratios (MRR) were estimated in Cox regression models for lung cancer as discrete and smoothed functions of cumulative exposure to synthetic MWF (mg/m3 per year) and years exposed to biocide with both synthetic and soluble MWF. The analysis was also restricted to the subcohort hired on or after 1941 and stratified by follow-up period. ' ' RESULTS ': 'The splines suggested a non-linear inverse exposure–response for lung cancer mortality with increasing endotoxin exposure. Overall, the greatest reduction in mortality was observed among those with the highest exposure [MRR 0.63, 95% confidence interval (95% CI) 0.39–0.98] at the 99th percentile of exposure (15.8 mg/m3 per year). Evidence for an inverse effect was limited to the earlier follow-up period. Effect modification by biocide was marginally significant (P=0.07); the protective effect of synthetic MWF was observed only for those who were co-exposed. ' ' CONCLUSIONS ': 'The protective effect of synthetic MWF against lung cancer mortality persisted through the extended period of follow-up, although attenuated, and was observed only among workers with co-exposure to biocide and synthetic MWF.
Keywords: auto manufacturing industry; biocide; cohort study; endotoxin; exposure; lung cancer; lung cancer mortality; metalworking fluid; mortality; occupational epidemiology; retrospective cohort study; synthetic biocide; synthetic fluid